2015
DOI: 10.4251/wjgo.v7.i7.55
|View full text |Cite
|
Sign up to set email alerts
|

Low rectal cancer: Sphincter preserving techniques-selection of patients, techniques and outcomes

Abstract: Low rectal cancer is traditionally treated by abdominoperineal resection. In recent years, several new techniques for the treatment of very low rectal cancer patients aiming to preserve the gastrointestinal continuity and to improve both the oncological as well as the functional outcomes, have been emerged. Literature suggest that when the intersphincteric resection is applied in T1-3 tumors located within 30-35 mm from the anal verge, is technically feasible, safe, with equal oncological outcomes compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 112 publications
(188 reference statements)
0
24
0
Order By: Relevance
“…Chemoradiotherapy improves survival rates and local recurrence by reducing tumour size and stage, and also has the ability to achieve pathologic downstaging [ 11 , 12 ]. For these reasons, neoadjuvant chemotherapy is the standard of care for stage II–III rectal tumours, not only to increase the effectiveness of radiotherapy but also to attain negative surgical margins [ 13 ] and enhance the possibility for sphincter-preserving surgery [ 14 ]. As described by Ryan et al, tumour regression grade is a useful method of scoring pathologic response to chemoradiotherapy in rectal carcinomas [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chemoradiotherapy improves survival rates and local recurrence by reducing tumour size and stage, and also has the ability to achieve pathologic downstaging [ 11 , 12 ]. For these reasons, neoadjuvant chemotherapy is the standard of care for stage II–III rectal tumours, not only to increase the effectiveness of radiotherapy but also to attain negative surgical margins [ 13 ] and enhance the possibility for sphincter-preserving surgery [ 14 ]. As described by Ryan et al, tumour regression grade is a useful method of scoring pathologic response to chemoradiotherapy in rectal carcinomas [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Martin et al the 5-year disease-free survival rate was 78.6% and the 5-year overall survival was 86.3% [15]. Oncological outcomes after ISR were not markedly different from those after APR with ranges of 68% -86% and 76% -97%, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…Kuo et al reported functional outcomes of ISR 38% had stool fragmentation, 23.8% had nocturnal defecation Saito et al mean Wexner score was 7.8. Kohler et al: Incontinence to flatus 23.8%, incontinence for liquid 29% and for solid stool 3.7%, Schiessel et al the mean stool frequency per 24 h was 2.6, Martin's et al [15] use of antidiarrheal medications (30%), Denost 7 urgency in 38%, Yoo et al use of hygiene pads (20%) [2]…”
Section: Discussionmentioning
confidence: 99%
“…emphasise that in order to assess the distance between the rectal tumour and the sphincter an MRI examination should be performed [9]. Proper evaluation of the stage of the disease and the location of the rectal tumour in respect to the anal sphincter is crucial for the possibility of surgical intervention that could spare that sphincter, thus preserving of the continuity of digestive tract and consequently the quality of life of the patient after the treatment is finished [10]. Owing to precise, effective MRI imaging in PET/MRI in the reported case, it was possible to pinpoint with better precision the depth of the intestinal wall infiltration by the rectal carcinoma.…”
Section: Discussionmentioning
confidence: 99%